Imperial perceptions of Palestine: Orientalism and colonialism in the Holy Land - Kamel, Lorenzo (I.B. Tauris, 2015)
From prophecies to empire -- The standard conquest myth -- The ownership of the land -- Zionism: beyond the either/or -- Zion--London: the Archimedean point -- Palestine's 'non-Jews' -- Mandate for Palestine: legitimizing the simplification process -- Divide and rule: the creation of the Transjordan Emirate -- Ḥajj Amīn al-Ḥusaynī and the Supreme Muslim Council: the Longa Manus of London -- Breaking the standardization process: getting back into history.